1987
DOI: 10.1007/bf00314286
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid immunoglobulins and virus-specific antibodies in disorders affecting the facial nerve

Abstract: Sixty-two patients with acute idiopathic peripheral facial nerve palsy (AIPFP) and 31 patients with lymphocytic meningoradiculitis (Garin-Bujadoux or Bannwarth's syndrome) are described. Results of cerebrospinal fluid (CSF) analysis, including the measurement of immunoglobulins (Ig) G, A, and M, indicate that pleocytosis and/or disturbance of the blood-CSF barrier (BCB) and/or local immunoglobulin synthesis within the central nervous system (CNS) do occur in about 25% of patients with AIPFP. The commonest find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The only positive result was reported by Sanstedt et al (2) who showed raised IgG index in children and claimed that facial palsy should be considered as a distinct entity in pediatric age. In another study pleocytosis, and/or local immunoglobulin synthesis, and/or blood-CSF barrier dysfunction did occur in 25% of AIPFP patients (8). Taken only as IgG index or oligoclonal band, the rate was much lower (10%).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The only positive result was reported by Sanstedt et al (2) who showed raised IgG index in children and claimed that facial palsy should be considered as a distinct entity in pediatric age. In another study pleocytosis, and/or local immunoglobulin synthesis, and/or blood-CSF barrier dysfunction did occur in 25% of AIPFP patients (8). Taken only as IgG index or oligoclonal band, the rate was much lower (10%).…”
Section: Discussionmentioning
confidence: 88%
“…Though no direct evidence could be obtained, raised HSV-1 antibodies in patients' sera might imply a viral infection and those cases presenting with only facial palsy should be forms frustes (1,13,(17)(18)(19)(20). Determining antibodies in CSF against various viruses may help specific diagnosis (8,14). Unfortunately no objective proof could be shown on viral etiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pleocytosis and previously undiagnosed Borreliosis have been among the abnormalities noted. A slightly impaired blood ÁCSF barrier was the most common pathological finding in two studies [8,9].…”
Section: Discussionmentioning
confidence: 98%
“…Lymphocytic meningoradiculoneuritis, or Bannwarth syndrome, can also be a cause of acute peripheral facial palsy. Approximately 50Yn of patients with the syndrome have facial palsy as well as other neurological symptoms (23,78,122,132,168,233,274,340). Wenig (342) observed peripheral facial palsy in 52 of 63 patients with chronic lymphocytic meningitis, among them 37 patients with bilateral manifestation.…”
Section: Acute Peripheral Facial Palsy In Childrenmentioning
confidence: 99%